The Revitalization of Sete de Setembro Avenue: The Potentialities of the New, a Criticism of the Present (Revista Brasileira Multidisciplinar, 2014)
This paper analyzes the one-off impact of a public policy in the city of Araraquara: the revitalization of Sete de Setembro Avenue. The particularity is related to the tensioned and ambivalent way with a myriad of complex phenomena. Our aim is to make some appointments from macro to micro, based on the theoretical analysis of some important intelectuals on the production and reproduction of urban space in the capitalist system and also from micro to macro - by direct observation and the application of a semi-structured questionnaire, with the aim to demonstrate the ambivalences that cross the social urban fabric aim of the revitalization process. In the Commercial Centre of Araraquara, the revitalization was an ambivalent process, in which structural changes are present in the same space. It was observed that a structural frailty may generate a social and economical barrier.
Keywords: Revitalization; Space production and reproduction; Spacial functionality; Ambivalence; Spacial transformation.